Accumulation of Unphosphorylated Calponin in the Submembranous Cytoskeletons of Arachidonic Acid-stimulated Human Platelets - Meyer, Thomas; Unterberg, Christina; Kreuzer, Heinrich; Buchwald, Arnd B (Thrombosis and Haemostasis, 1996)
Calponin, a basic smooth-muscle protein capable of binding to F-actin, tropomyosin and calmodulin in vitro, was tested for its expression and subcellular localization in resting and stimulated human platelets. Using immunoblotting techniques calponin was revealed as a single protein band with a molecular weight of 34 kDa. Although calponin has been shown to be proteolytically degraded by calpain, in the presence of the calpain inhibitor E-64 and EGTA a significant hydrolysis of calponin could not be detected. Upon stimulation with 10 μM arachidonic acid calponin became increasingly incorporated into Triton X-100 insoluble cytoskeletal fractions reaching a plateau after 15 s. The accumulation of calponin in the cytoskeletons of stimulated platelets paralleled the polymerization of actin into newly formed microfilaments. Immunofluorescence microscopy revealed a sub-membranous co-localization of calponin and actin in aggregated platelets. Since isolated calponin is phosphorylated by protein kinase C and Ca2+/calmodulin-dependent protein kinase II thereby losing its inhibitory effect on the actomyosin MgATPase activity, we examined whether changes in cell shape due to platelet stimulation are accompanied by a phosphorylation of calponin. By performing immunoblotting analysis on either resting or stimulated platelets phosphorylation of calponin on tyrosine, serine or threonine residues could not be demonstrated. In line, [32P]radiolabeling experiments were unable to detect phosphate incorporation into calponin. These observations support the hypothesis that calponin plays a physiological role in regulating contraction and secretion of human platelets even in the absence of its phosphorylation.